Leveraging Developing Economies With the Use of Information Technology 2012
DOI: 10.4018/978-1-4666-1637-0.ch009
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce Adoption in Nigerian Businesses

Abstract: Business organizations around the world engage in e-commerce (EC) and e-business to support business operations and enhance revenue generation from non-traditional sources. Studies focusing on EC adoption in Sub Saharan Africa (SSA) are just beginning to emerge in the extant information systems (IS) literature. The objective of this current study is to investigate factors impacting the acceptance of EC in small businesses in SSA with Nigeria as an example. A research model based on the Diffusion of Innovation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Relative advantage is one of the technical characteristics most used in e-commerce adoption studies in various contexts (Ghobakhloo & Tang, 2013;Sin et al, 2016;Ahmad et al, 2014). Alam et al (2014), Sin et al (2016), andEkong et al (2012) found that relative advantage has a significant positive effect on the adoption of e-commerce. Ghobakhloo et al (2010) suggested that the higher the perceived benefits of e-commerce, the more likely an SME will adopt it.…”
Section: Perceived Relative Advantagementioning
confidence: 99%
See 4 more Smart Citations
“…Relative advantage is one of the technical characteristics most used in e-commerce adoption studies in various contexts (Ghobakhloo & Tang, 2013;Sin et al, 2016;Ahmad et al, 2014). Alam et al (2014), Sin et al (2016), andEkong et al (2012) found that relative advantage has a significant positive effect on the adoption of e-commerce. Ghobakhloo et al (2010) suggested that the higher the perceived benefits of e-commerce, the more likely an SME will adopt it.…”
Section: Perceived Relative Advantagementioning
confidence: 99%
“…Pressure from suppliers and customers refers to the degree to which a company or SME is pressured to adapt e-commerce due to the awareness and the culture of its customers or suppliers (Rahayu & Day, 2015) and their demand for the implementation of e-commerce in doing business (Ekong et al, 2012). In the other words, SMEs may adopt e-commerce technology due to pressure from their customers or suppliers (Sin et al, 2016;Olatokun & Kebonye, 2010).…”
Section: Pressure From Suppliers or Customersmentioning
confidence: 99%
See 3 more Smart Citations